1999
DOI: 10.1093/jnci/91.23.2038
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Amine Content of Cooked Meat and Risk of Prostate Cancer

Abstract: Meat doneness and estimated intake of heterocyclic amines from cooked meat were not clearly associated with prostate cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 18 publications
4
100
0
1
Order By: Relevance
“…Epidemiological studies have revealed a link between prostate cancer incidence and mortality and the consumption of red meat and animal fats [62][63][64] . One mechanism by which meats might stimulate cancer development could be related to the formation of hetero cyclic amines (HCAs) 65 .…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Epidemiological studies have revealed a link between prostate cancer incidence and mortality and the consumption of red meat and animal fats [62][63][64] . One mechanism by which meats might stimulate cancer development could be related to the formation of hetero cyclic amines (HCAs) 65 .…”
Section: Dietary Factorsmentioning
confidence: 99%
“…However, recent epidemiological studies concerning HCA intake gave conflicting results. While casecontrol studies conducted in Uruguay and in the USA showed positive correlations between the intake of HCA and the risk of breast (Sinha et al, 2000a;De Stefani et al, 1997b), colon (Sinha et al, 2001;De Stefani et al, 1997a), lung (Sinha et al, 2000b), and gastric cancer (De Stefani et al, 1998a), other groups were not able to detect any association between the intake of HCA and the cancer risk of different sites (Norrish et al, 1999;Augustsson et al, 1999b;Lyon & Mahoney, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…During recent decades, a possible relationship between the methods of meat and fish preparation and the risk of cancer development of different sites has been observed in epidemiological studies (Sinha et al, ,2000a(Sinha et al, ,b,2001Deitz et al, 2000;Norrish et al, 1999;Zheng et al, 1999;De Stefani et al, 1997a,b,1998aProbst-Hensch et al, 1997;Ward et al, 1997;Schiffman & Felton, 1990;Steineck et al, 1990). It has been suggested that heterocyclic amines (HCA) may explain at least some of the observed effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased risks of colorectal adenoma and adenocarcinoma, and of stomach, breast, lung and PCs have been weakly or clearly associated with potential or estimated HA exposure in most ( Shiffman and Felton, 1990;Gerhardsson de Verdier et al, 1991;Lang et al, 1994;Probst -Hensch et al, 1997;Ward et al, 1997;Kampman et al, 1999;Norrish et al, 1999;Sinha et al, 1998aSinha et al, , 1999Zheng et al, 1998Zheng et al, , 1999, but not all (Lyon and Mahoney, 1988;Muscat and Wynder, 1994;Augustsson et al, 1999 ), case ± control studies investigating possible associations between increased human cancer risk and dietary HA -exposure categories based on self -reported meat -cooking methods and meat -doneness preferences. Positive studies have tended to be those in which interactions among meat types, intake frequencies, cooking methods and /or cooking doneness preferences were reflected in the categories used to classify relative HA -exposure levels (Probst -Hensch et al, 1997;Ward et al, 1997;Sinha et al, 1998bSinha et al, , 1999Zheng et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%